TINJAUAN PEMBELAJARAN PADA MATA KULIAH PRAKTIK SECARA DARING DI MASA PANDEMI COVID-19 JURUSAN TATA RIAS DAN KECANTIKAN - Elsa Arista; Merita Yanita (Universitas Negeri Padang, 2022)
This study aims to describe the opinions of students majoring in make-up and beauty regarding practical lectures that are carried out boldly in terms of the teaching and learning process, the capabilities of the lecturers, and practical facilities and infrastructure. This type of research is descriptive quantitative. The research sample was 46 students majoring in make-up and beauty, of whom 21 students from class 2018 and 25 students from class 2019. The research variable is a single variable. The research instrument used a questionnaire with a Likert scale which stated as many as 60 items. The research data were analyzed using descriptive analysis of proportions using SPSS 20. The results showed that student learning was as big as make-up and beauty towards practical subjects 77.95% boldly with moderate criteria. Student learning review includes 3 indicators in the form of practical learning and teaching processes, lecturer capabilities, practical facilities and infrastructure. Student learning of practical subjects as seen from the indicators of the teaching and learning process with a result of 80.40% with good criteria. Student learning towards practical subjects is boldly seen in terms of lecturer capability (lecturer competence) with a result of 82.13% with a good category. And student learning towards practical subjects was boldly seen in terms of practical facilities and infrastructure with a result of 71.32% in the moderate category. Based on the results of research for research for students to carry out practical lectures in a bold and serious manner by providing practical facilities and infrastructure so that the practices we carry out boldly can be carried out in accordance with the objectives of the lecture.